Literary history of Canada : Canadian literature in English. - Klinck, Carl F. (Carl Frederick), 1908-1990; Bailey, Alfred Goldsworthy, 1905- (University of Toronto Press, 1976)
This major effort of a large group of scholars working in the field of English-language Canadian literature provides a comprehensive, up-to-date reference work. It represents a positive attempt to give a history of Canada in terms of writings which deserve attention because of significant thought, form, and use of language.